Connecting air freight services with the road transport network, Case: FREJA Transport & Logistics Oy - Raita, Juhani (My University, 2017)
This master’s thesis is made as a commission for FREJA Transport & Logistics Oy. Aim of the thesis is to research how the current export air freight process can be improved with DMAIC cycle. Export air freight process needed improvement because process was mostly outsourced and company’s own resources used poorly. Research is limited to consider only export air transports from Finland to outside Europe. Theoretical part of the research was divided to two separate sections. First section handled the concept of business process improvement, which included such issues as Six Sigma, DMAIC cycle, and SCOR metrics. Second section of the theoretical part considered air freight. Air freight was discussed through six themes: demand for air cargo, aircrafts, transport units, air cargo operators, air freight costs, and future in the market. Lastly a common export air freight process was comprised and explained to set basis for the empirical part. In the empirical part, process was improved step by step as per the DMAIC cycle to reveal the issues causing the limited use of own resources. Main reason for variation and inefficient use of resources was outsourcing and by that linking number of intermediaries in the process. The solution was to insource the road transportation from the consignor to the gateway airport. Results revealed that operating costs can be reduced with the improved process and still offer evenly competitive service. Results of the empirical part were validated by process charts, profitability calculations and other supporting documentation created during the DMAIC cycle.
Keywords: Air freight; Business process improvement; DMAIC; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|